PENGARUH GUIDED INQUIRY BERBANTUAN PhET SIMULATIONS TERHADAP HASIL BELAJAR SISWA SMA PADA POKOK BAHASAN USAHA DAN ENERGI - Khofifatul Rasyidah; Supeno Supeno; Maryani Maryani (JURNAL PEMBELAJARAN FISIKA, 2018)
Abstract The purpose of this study was to determine the effect of guided inquiry learningmodel on the student cognitive learning outcomes of high school students on work andenergy subject. This research was used experimental method with designnonequivalent control group design. The population were all students of X class ofMIPA in SMA Negeri 4 Jember. The sample was obtained by purposive sampling areatechnique were X MIPA 5 as experiment class and X MIPA 3 as control class. Thedata was collected based on the student cognitive learning outcomes through pre-testand post-test scores. The data were analyzed using Independent Sample T-Test. Theresult showed that guided inquiry learning model with PhET Simulations has nosignificant effect on the student cognitive learning outcomes of high school students. Keywords: the student cognitive learning outcomes, inquiry, PhET Simulations.